(untitled) - Lougheed, Lin (New York, 2014)
IELTS test takers must have a command of English vocabulary that applies to many different situations and contexts. This book offers students extensive practice in vocabulary building and correct English usage, with emphasis on 600 English words that relate to specific categories that appear frequently on IELTS exams. These categories include nature and the environment, leisure activities and hobbies, the arts and culture, transportation, health, tourism, business, technology, social issues, and education.
Keywords: English language,International English Language Testing System,International English Language Testing System,International English Language Testing System,International English Language Testing System,Vocabulary,English language,Từ vựng,Tiếng Anh,Tiếng Anh,Hệ thống kiểm tra ngôn ngữ tiếng Anh quốc tế,International English Language Testing System; Spoken English,Nói tiếng Anh